Leave No One Behind How are Development Assistance Committee members answering the pledge of the 2030 Agenda for Sustainable Development? - Di Francesco, Beatrice (OECD Publishing, 2018)
In 2015, UN Member States and the international community more broadly endorsed the 2030 Agenda for Sustainable Development and the Agenda's commitment to achieve the Sustainable Development Goals for everyone to leave no one behind. This working paper presents and analyses the findings of a survey circulated to members of the OECD's Development Assistance Committee (DAC) between April and May 2018. The survey investigated the level and extent of commitment to leave no one behind in development co-operation policies, strategies and programming. It also gathered views and evidence from DAC members about the comparative advantage, opportunities, challenges and strategies for answering this pledge of the 2030 Agenda for Sustainable Development. The findings presented in this paper inform the analysis of the 2018 Development Co-operation Report: Joining Forces to Leave No One Behind
Keywords: Development